Restorative Justice in the World of Sports: Realizing Sportsmanship and Morality of Athletes through Penal Mediation - Paramitha, Sandey Tantra; Priyatno, Dwidja; Januarsyah, Mas Putra Zenno (Universitas PGRI Kanjuruhan Malang, 2025)
The purpose of this study is to examine the implementation of the restorative justice approach in the context of sports law as an alternative dispute resolution involving ethical and moral violations by athletes. The research method uses a qualitative approach through literature studies and case analysis, this study identifies how penal mediation can be an instrument to realize the values ​​of sportsmanship and athlete morality. The data in this study were obtained through three data collection methods, namely literature studies of regulations, academic literature, and documentation of sports conflict cases carried out by referring to the principles of systematic literature review. Then the data analysis uses thematic analysis methods involving several stages, namely familiarization with data, initial coding, identification of potential themes, review of themes, definition and naming of themes, to report production. The results of the study indicate that the restorative justice approach through penal mediation has significant potential in overcoming sports conflicts by facilitating dialogue, accountability, and rehabilitation, while strengthening the values ​​of sportsmanship, so that it is able to answer the need for a more just, humanistic, and contextual conflict resolution mechanism.